PEMAHAMAN MATEMATIKA: PENERAPAN MODEL ARCS DAN PENILAIAN KINERJA - Diah Arum Kartikasari (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2018)
This study aims to determine the effect of ARCS model and performance appraisal on students' mathematical understanding. The sample in this research is VII students of SMP Negeri 2 Toboali. The dependent variable is a mathematical understanding, and the independent variables consist of the differentiated learning models being ARCS and conventional, and the assessment techniques are differentiated into performance and written tests. The instrument used is the students' mathematical comprehension test. The method used is quasi experimental method with 2x2 factorial design. The results of this study indicate that students 'mathematical understanding using the ARCS model will be more effective if given a performance assessment, and students' mathematical understanding using conventional models will be more effective if given a written test assessment.